Fresno-Merced Counties Legal Services Christmas Party at Patience Milrod's Home - Watkins, Howard::::::::: (1980)
Robert Higgins handing wine glass to Nancy Currier, Scott Williams, David Cisneros 3400 Block of E. Montecito Avenue